The Effectiveness of An Appreciated Inquiry-Based Intervention to Improve Nursing Handover Process: A Queasy Experimental Study - Lindayani, Linlin; Yetti, Krisna (Universitas Pendidikan Indonesia, 2021)
Introduction: Many interventions were developed to improve the handover process, but most of them were generally target information transfer directly, individual behavior, or the more comprehensive system. Objectives : The purpose of this study was to evaluate the effectiveness of an appreciated inquiry based on improving the handover process among nurses in the medical-surgical ward, Indonesia. Methods: A quasi-experimental with one group pre-test and post-test design was conducted at a medical-surgical ward at a tertiary hospital in Jakarta, Indonesia. Results: A total of 36 nurses participated in this study, including the head and registered nurse. The intervention was designed to improve the implementation of the handover process among nurses in the medical-surgical ward based on the philosophy of appreciated inquiry using four learning activities. A total of 36 nurses were joined in the study. The handover process was done on time for more than 90%, the proportion of leadership was increased 13% become 95% from 82%.Further, the use of the SBAR communication pattern improved significantly from 72% to 89%, and documentation of handover using SBAR was increased by about 20%. Discussion: The tailored intervention based on appreciated inquiry was effectively to improve the quality of the handover process, including implementation of handovers on time, and ethical leadership, communication, and documentation. Nursing management needs to continue the intervention to optimize the role and function of nurses in handover.ABSTRAKPendahuluan: Banyak intervensi dikembangkan untuk meningkatkan proses serah terima, tetapi kebanyakan dari intervensi tersebut umumnya merupakan transfer informasi target secara langsung, perilaku individu, atau sistem yang lebih komprehensif. Tujuan: Tujuan dari penelitian ini adalah untuk mengevaluasi efektivitas penyelidikan yang dihargai berdasarkan peningkatan proses serah terima pada perawat di bangsal bedah medis, Indonesia. Metode: Sebuah eksperimen semu dengan desain pre-test dan post-test satu kelompok dilakukan di bangsal bedah-medik di sebuah rumah sakit tersier di Jakarta, Indonesia. Hasil: Sebanyak 36 perawat berpartisipasi dalam penelitian ini, termasuk kepala dan perawat. Intervensi dirancang untuk meningkatkan pelaksanaan proses serah terima di antara perawat di bangsal bedah medis berdasarkan filosofi inkuiri dihargai dengan menggunakan empat kegiatan pembelajaran. Sebanyak 36 perawat bergabung dalam penelitian ini. Proses serah terima dilakukan tepat waktu lebih dari 90%, proporsi kepemimpinan meningkat 13% menjadi 95% dari 82%. Selanjutnya, penggunaan pola komunikasi SBAR meningkat secara signifikan dari 72% menjadi 89%, dan dokumentasi serah terima menggunakan SBAR meningkat sekitar 20%. Diskusi: Intervensi yang disesuaikan berdasarkan penyelidikan yang diapresiasi efektif untuk meningkatkan kualitas proses serah terima, termasuk pelaksanaan serah terima tepat waktu, dan kepemimpinan etis, komunikasi, dan dokumentasi. Manajemen keperawatan perlu melanjutkan intervensi untuk mengoptimalkan peran dan fungsi perawat dalam serah terima.